I am Sam [love is all you need] - Bedford Falls Company; New Line Cinema Corporation; Red Fish, Blue Fish Films (Firm).; New Line Home Entertainment (Firm). ([United States] New Line Home Entertainment, 2002)
Sam Dawson has the mental capacity of a 7-year-old. He works at a Starbucks and is obsessed with the Beatles. He has a daughter with a homeless woman; she abandons them as soon as they leave the hospital. He names his daughter Lucy Diamond (after the Beatles song), and raises her. But as she reaches age 7 herself, Sam's limitations start to become a problem at school; she's intentionally holding back to avoid looking smarter than him. The authorities take her away, and Sam shames high-priced lawyer Rita Harrison into taking his case pro bono. In the process, he teaches her a great deal about love, and whether it's really all you need.
Information from pre-release promotional materials; release date: June 18, 2002.
Originally produced as a motion picture in 2001.
Cinematography, Elliot Davis ; editor, Richard Chew ; music, John Powell.
Sean Penn, Michelle Pfeiffer, Dakota Fanning.
DVD videos, NTSC region 3.
Keywords: People with mental disabilities -- Drama; Custody of children -- Drama; Video recordings for the hearing impaired